Effectiveness of electroacupuncture for the treatment of refractory overactive bladder disease in women: study protocol for a randomised controlled clinical trial - Shuo Zhang; Yulong Ding; Yuan Ji; Huai-Yu Wang; Hong-Chao Zhao (BMJ Open, 2025)
Introduction Overactive bladder (OAB) is a common condition, affecting approximately one-fifth to one-sixth of the world’s population. The American Urological Association and the Society of Urodynamics, Female Pelvic Medicine and Genitourinary Reconstruction guidelines recommend sacral neuromodulation (SNM) as third-line treatment. Although SNM can relieve the symptoms of refractory OAB, several factors, including high cost and the high incidence of adverse effects, limit its large-scale clinical use. Moreover, patient acceptance is low. Acupuncture is an alternative approach for treating OAB that is minimally invasive and has few side effects. Clinical studies have shown that it can reduce the number of episodes of urination and urgent urination within 24 hours and improve the quality of life. However, clinical evidence on the effectiveness of electroacupuncture for treating refractory OAB is limited.The primary objective of this study Is to assess the short-term effectiveness of electroacupuncture for improving the symptoms and quality of life of women with refractory OAB and to observe its long-term effects. A secondary objective is to assess whether electroacupuncture is more effective than conventional acupuncture for treating patients with refractory OAB.Methods and analysis The study is designed as a two-arm, parallel, participant-blinded randomised controlled trial (RCT). A total of 60 women between the ages of 18 years and 60 years who are experiencing refractory OAB will be randomly assigned to two groups: one receiving electroacupuncture and the other receiving conventional acupuncture. Each participant will undergo a treatment regimen lasting 4 weeks. During the initial 2 weeks, participants will receive five sessions of either electroacupuncture or conventional acupuncture per week, followed by three sessions per week during the subsequent 2 weeks. In total, each individual will receive 16 treatment sessions throughout the course of the study. The primary outcome measure will be the change in OAB Symptom Score (OABSS) over time between groups. The secondary outcome measures will include the OABSS, the Patient-Perceived Bladder Symptom Grading Scale, the Overactive Bladder Questionnaire, the Self-Rating Anxiety Scale and the Self-Rating Depression Scale during the treatment and follow-up periods. Blinding and safety will also be assessed. Two-sided p values <0.05 will be considered statistically significant.Ethics and dissemination The study protocol was approved by the Institutional Review Board of Beijing Fengtai Hospital of Integrated Traditional and Western Medicine on 5 February 2024 (Approval No. 2024020101). The results will be disseminated through presentations at scientific conferences and peer-reviewed publications.Trial registration number ChiCTR2400081448.